Risk analysis of enfortumab vedotin: A real-world approach based on the FAERS database - Fuchun Zheng; Yuanzhuo Du; Yuyang Yuan; Zhipeng Wang; Sheng Li; Situ Xiong; Jin Zeng; Yifan Tan; Xiaoqiang Liu; Songhui Xu; Bin Fu; Wei Liu (Heliyon, 2024)
Purpose: To analyze the risk of enfortumab vedotin (EV), a targeted therapy for advanced bladder cancer, using real-world data from the U.S. Food and Drug Administration's Federal Adverse Event Reporting System (FAERS). Methods: A retrospective pharmacovigilance analysis was conducted using FAERS data from Q1 2020 to Q1 2024. Adverse drug events (ADEs) related to EV were identified and categorized according to the System Organ Classes (SOCs) and specific events. Statistical methods, such as the proportional reporting ratio, reporting odds ratio (ROR), Bayesian confidence propagation neural network, and empirical Bayesian geometric mean were used to detect safety signals. Results: Of the 7,449,181 FAERS case reports, 1,617 EV-related ADEs were identified, including 101 preferred terms and 22 SOCs. The key SOCs included skin and subcutaneous tissue, metabolic, and nutritional disorders. Rare ADEs, such as lichenoid keratosis (n = 4; ROR 26.89), small intestinal perforation (n = 3; ROR 24.51), pigmentation disorder (n = 9; ROR 18.16), and cholangitis (n = 8; ROR 17.48), showed significant disproportionality. Conclusion: While most findings aligned with the existing data, new signs such as lichenoid keratosis and small intestinal perforation were identified. Further studies are necessary to validate these findings and emphasize the need for the clinical monitoring of EV-related ADEs.